1992
DOI: 10.1055/s-2006-961385
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenanthridine Alkaloids Isolated fromEschscholtzia californicaCell Suspension Cultures Interact with Vasopressin (V1) Receptors

Abstract: Chelerythrine and sanguinarine, two benzophenanthridine alkaloids, have been isolated from a crude methanolic extract of Eschscholtzia californica cell suspension cultures by successive fractionations. These two molecules exhibited affinity for rat liver vasopressin V1 receptors and are competitive inhibitors of [3H]-vasopressin binding within the micromolar range (Ki). Chelerythrine and sanguinarine represent two of the first non-peptidic structures providing original chemical leads for the design of syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Cellular studies suggest that topoisomerase I is the major cytotoxic target for nitidine [114,117]. However, it is worth to bear in mind that benzophenanthridine alkaloids have been reported to mediate a variety of biological activity, including potent and selective inhibition of protein kinase C, binding to vasopressin V1 receptor, inhibition of taxol-mediated polymerization of tubulin and inhibition of cholinesterase systems, to cite only a few of them [118][119][120][121]. Therefore the antileukemic activity of nitidine may be due to the inhibition of topoisomerases and/or microtubule function.…”
Section: Inhibition Of Topoisomerase I By Dna Binding Drugsmentioning
confidence: 99%
“…Cellular studies suggest that topoisomerase I is the major cytotoxic target for nitidine [114,117]. However, it is worth to bear in mind that benzophenanthridine alkaloids have been reported to mediate a variety of biological activity, including potent and selective inhibition of protein kinase C, binding to vasopressin V1 receptor, inhibition of taxol-mediated polymerization of tubulin and inhibition of cholinesterase systems, to cite only a few of them [118][119][120][121]. Therefore the antileukemic activity of nitidine may be due to the inhibition of topoisomerases and/or microtubule function.…”
Section: Inhibition Of Topoisomerase I By Dna Binding Drugsmentioning
confidence: 99%
“…Benzo [c]phenanthridine alkaloids have a number of interesting pharmacological activities including antiviral [9], antitumoral [10], antimicrobial [11], antifungal [12] and anti-inflammatory properties [13]. They have also been shown to inhibit phosphorylation of proteins in the mitochondrial fraction of the rat heart [14]) and [ 3 H]-vasopressin binding [15]. They may also interact with biopolymers by mean of their reactive iminium group and intercalating in this way DNA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Arginine vasopressin (AVP) interacts with three subtypes of vasopressin receptors, V 1 , V 2 , and V 3 , mediating vasoconstriction, water reabsorption, and central nervous system effects, respectively (Treschan and Peters 2006). In 1992, Granger et al showed that SA isolated from Eschscholtzia californica ; competitively inhibited binding of AVP to V 1 receptors (Granger et al 1992). In rat liver plasma membranes SA competed dose‐dependently for binding to V 1 receptors with an IC 50 of 2.6 × 10 −5 M. The IC 50 was determined by the inhibition of agonist, [ 3 H]AVP‐specific binding using increasing concentrations of SA.…”
Section: Pharmacologymentioning
confidence: 99%